SCREENING AND MOLECULAR ANALYSIS OF SOME RICE (Oryza sativa L.) GENOTYPES FOR DROUGHT TOLERANCE AT SEEDLING STAGE - R. Anik; M. A. Islam; M. I. Uddin; M. M. Islam; M. Harun-or Rashid; M. M. Hossain; S. Razia; M. S. Haque (Journal of Animal and Plant Sciences, 2021)
Drought is one of the major abiotic constraints for rice grown under the rain-fed condition and causes a substantial reduction in yield. It has now become a severe threat to food security in the developing world including Bangladesh. We used 30 rice genotypes of diverse geographical origins including 2 drought-tolerant check varieties, NERICA-1 and NERICA-10, to screen under drought stress and to evaluate simple sequence repeat (SSR) markers for identifying drought-tolerant rice genotypes at the seedling stage. The screening was done by a hydroponic method using polyethylene glycol (PEG 6000). Three drought stress levels, -0.66, -1.03 and -1.48 bars of water potential ware imposed using 6%, 8% and 10% PEG, respectively. Control was maintained using the only nutrient solution. Genotypes were scored based on IRRI standard evaluation score for visual stress injury and data were collected on root length, shoot length and root/shoot ratio at three different levels of treatments along with control. A total of 86 alleles were detected among 30 rice genotypes by using 20 SSR markers. The polymorphic information content (PIC) values ranged from 0.11(RM28502) to 0.84 (RM562) with an average of 0.58 and gene diversity value ranged from 0.88 (RM25022) to 0.23 (RM28502) with an average of 0.63. The SSR markers successfully separated drough-tolerant varieties in four different groups. Combining molecular assessment with morphological findings it was accomplished that FR13A was highly drought-tolerant, Sadamota was moderate drought-tolerant and Baichmon, Q-31, BRRI dhan48, Binadhan-17 and BRRI dhan46 were low drought tolerant genotypes. This information could be used for the selection of suitable parents to develop drought-tolerant rice varieties using marker-assisted back crossing program.
Keywords: Drought; In vitro screening; PEG; Rice; SSR markers